2020
DOI: 10.12968/bjon.2020.29.20.1178
|View full text |Cite
|
Sign up to set email alerts
|

Setting up a successful nurse-led intravitreal injections service: pearls from Swindon

Abstract: The demand for performing intravitreal injections has increased in recent years, prompting the need for more nurse training in their administration. The Great Western Hospitals NHS Trust in Swindon has developed a structured nurse training programme and now has 8 independent nurse injectors trained to undertake injections independently; nurse practitioners now contribute upwards of 85% of the total number of injections. The authors have also demonstrated the financial benefits of using injection assistant devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Another study ( Duncan et al., 2017 ) that was conducted in Australia found that through the government initiative to train nurses to perform endoscopic procedures, a successful expansion of their surgical capacity ensued. Furthermore, the results of the 12 studies that initiated a local nurse-surgeon training and education programme within their hospitals were consistent in reporting the positive impact of nurse-led surgery models of care in terms of the improvement in the surgical waitlist and the timely provision of essential surgical services ( Hasan et al., 2020 ; Gallagher, 2017 ; Shum et al., 2010 ; Hickey et al., 2009 ; Goodfellow et al., 2003 ; Duthie et al., 1998 ; Moshakis et al., 1996 ; Spiegel, 1995 ; Maule, 1994 ; DiSario and Sanowski, 1993 ; White et al., 1987 ; Rosevelt et al., 1984 ). Although the aim of our review was to identify and describe the current methods of nurse-surgeon training and education, the discussion of our findings regarding its implementation history is also vital particularly in leveraging the potential of nurse-surgeons to the international and national key stakeholders.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Another study ( Duncan et al., 2017 ) that was conducted in Australia found that through the government initiative to train nurses to perform endoscopic procedures, a successful expansion of their surgical capacity ensued. Furthermore, the results of the 12 studies that initiated a local nurse-surgeon training and education programme within their hospitals were consistent in reporting the positive impact of nurse-led surgery models of care in terms of the improvement in the surgical waitlist and the timely provision of essential surgical services ( Hasan et al., 2020 ; Gallagher, 2017 ; Shum et al., 2010 ; Hickey et al., 2009 ; Goodfellow et al., 2003 ; Duthie et al., 1998 ; Moshakis et al., 1996 ; Spiegel, 1995 ; Maule, 1994 ; DiSario and Sanowski, 1993 ; White et al., 1987 ; Rosevelt et al., 1984 ). Although the aim of our review was to identify and describe the current methods of nurse-surgeon training and education, the discussion of our findings regarding its implementation history is also vital particularly in leveraging the potential of nurse-surgeons to the international and national key stakeholders.…”
Section: Discussionmentioning
confidence: 70%
“…(1998) United Kingdom Quantitative descriptive To design and evaluate a training programme for nurse endoscopists 215 colorectal patients examined by trained nurse practitioner 215 Hospital Endoscopy Unit Training hospital Gastroenterology (flexible sigmoidoscopy) Not stated Gallagher (2017) United Kingdom Quantitative descriptive To determine the patient satisfaction of patients having nurse led intravitreal therapy 100 patients undergoing nurse led intravitreal therapy 100 Hospital Day Surgery Training hospital Ophthalmology (intravitreal therapy) Not stated Goodfellow et al. (2003) United Kingdom Quantitative descriptive To describe the first full year of independent practice by a newly appointed nurse endoscopist in a district general hospital in the United Kingdom 282 patients who underwent nurse-led flexible sigmoidoscopy 282 Hospital Endoscopy Unit Training hospital Gastroenterology (flexible sigmoidoscopy) Not stated Hasan et al. (2020) United Kingdom Quantitative descriptive To describe the Swindon model of training nurses to be independent intravitreal therapy injectors 22 ophthalmic nurses Not stated Hospital Day Surgery Training hospital Ophthalmology (intravitreal therapy) Not stated Hickey et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The department also developed a 12-week training pathway for nurses from induction session to delivering independent intravitreal injection session 13 . Between 2015 and 2020, the number of nurse injectors in the department increased from three to seven while maintaining the standard of injections and keeping patients’ satisfaction at a high level 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment takes the form of intravitreal injections (IVIs) of anti-vascular endothelial growth factor (anti-VEGF) agents which are recommended for variable periods of time and at varying intervals depending on changes in the retina observed through OCT 15 16. While the decisions about treatments often involve ophthalmologists, the injections themselves are increasingly performed independently by specialised nurse practitioners and allied health professionals 17 18. Given the highly protocolised, OCT-dependent, nAMD treatment pathway and pre-existent clinical AI capable of independently quantifying the OCT features which inform that treatment, there is a clear opportunity for AI-enabled nAMD services to expand capacity and reduce avoidable real-world sight loss 12 16…”
Section: Introductionmentioning
confidence: 99%